On the Singular Loci and the Images of Proper Holomorphic Maps From Pseudoellipsoids - Giannotti, Cristina; Spiro, Andrea (Mathematica Scandinavica, 2015)
We prove a generalisation of Rudin's theorem on proper holomorphic maps from the unit ball to the case of proper holomorphic maps from pseudoellipsoids.